Functional network mediates age‐related differences in reaction time: a replication and extension study. Issue 5 (13th March 2015) - Gazes, Yunglin; Habeck, Christian; O'Shea, Deirdre; Razlighi, Qolamreza R.; Steffener, Jason; Stern, Yaakov
Abstract Introduction A functional activation (i.e., ordinal trend) pattern was previously identified in both young and older adults during task‐switching performance, the expression of which correlated with reaction time. The current study aimed to (1) replicate this functional activation pattern in a new group of fMRI activation data, and (2) extend the previous study by specifically examining whether the effect of aging on reaction time can be explained by differences in the activation of the functional activation pattern. Method A total of 47 young and 50 older participants were included in the extension analysis. Participants performed task‐switching as the activation task and were cued by the color of the stimulus for the task to be performed in each block. To test for replication, two approaches were implemented. The first approach tested the replicability of the predictive power of the previously identified functional activation pattern by forward applying the pattern to the Study II data and the second approach was rederivation of the activation pattern in the Study II data. Results Both approaches showed successful replication in the new data set. Using mediation analysis, expression of the pattern from the first approach was found to partially mediate age‐related effects on reaction time such that older age was associated with greater activation of the brain pattern and longer reaction time, suggesting that brain activation efficiency (defined as "the rate of activation increase with increasing task difficulty" in Neuropsychologia 47, 2009, 2015) of the regions in the Ordinal trend pattern directly accounts for age‐related differences in task performance. Discussion The successful replication of the functional activation pattern demonstrates the versatility of the Ordinal Trend Canonical Variates Analysis, and the ability to summarize each participant's brain activation map into one number provides a useful metric in multimodal analysis as well as cross‐study comparisons.